Coronavirus Immunotherapeutic Consortium Database. (10th February 2023) - Mahita, Jarjapu; Ha, Brendan; Gambiez, Anais; Schendel, Sharon L; Li, Haoyang; Hastie, Kathryn M; Dennison, S Moses; Li, Kan; Kuzmina, Natalia; Periasamy, Sivakumar; Bukreyev, Alexander; Munt, Jennifer E; et al.
Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has seen multiple anti-SARS-CoV-2 antibodies being generated globally. It is difficult, however, to assemble a useful compendium of these biological properties if they are derived from experimental measurements performed at different sites under different experimental conditions. The Coronavirus Immunotherapeutic Consortium (COVIC) circumvents these issues by experimentally testing blinded antibodies side by side for several functional activities. To collect these data in a consistent fashion and make it publicly available, we established the COVIC database (COVIC-DB, https://covicdb.lji.org/ ). This database enables systematic analysis and interpretation of this large-scale dataset by providing a comprehensive view of various features such as affinity, neutralization, in vivo protection and effector functions for each antibody. Interactive graphs enable direct comparisons of antibodies based on select functional properties. We demonstrate how the COVIC-DB can be utilized to examine relationships among antibody features, thereby guiding the design of therapeutic antibody cocktails. Database URL https://covicdb.lji.org/